Synthesis, crystal structure and Hirshfeld surface analysis of a zinc(II) coordination polymer of 5-phenyl-1,3,4-oxadiazole-2-thiolate - Pirimova, Mehribon; Torambetov, Batirbay; Kadirova, Shakhnoza; Ziyaev, Abdukhakim; Gonnade, Rajesh G.; Ashurov, Jamshid (Acta Crystallographica Section E Crystallographic Communications, 2022)
A new zinc coordination polymer with 5-phenyl-1,3,4-oxadiazole-2-thiolate, namely, catena-poly[zinc(II)-bis(μ2-5-phenyl-1,3,4-oxadiazole-2-thiolato)-κ2N3:S;κ2S:N3], [Zn(C8H5N2OS)2]n, was synthesized. The single-crystal X-ray <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/D01712.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">diffraction analysis shows that the polymeric structure crystallizes in the centrosymmetric monoclinic C2/c <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Space_group" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">space group. The ZnII atom is coordinated to two S and two N atoms from four crystallographically independent (L) ligands, forming zigzag chains along the [001] direction. This polymer complex forms an eight-membered [Zn–S–C–N–Zn–S–C–N] chair-like ring with two ZnII atoms and two ligand molecules. On the Hirshfeld surface, the largest contributions come from the short contacts such as <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/V06597.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">van der Waals forces, including H⋯H, C⋯H and S⋯H. Interactions including N⋯H, O⋯H and C⋯C contacts were also observed; however, their contribution to the overall stability of the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Lattice" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">crystal lattice is minor.
Keywords: 3; 4-oxadiazole-2-thiol; coordination polymer; Hirshfeld surface analysis; crystal structure; zinc complex; 5-phenyl-1